A Sub-6 nm MnFe2O4-dichloroacetic acid nanocomposite modulates tumor metabolism and catabolism for reversing tumor immunosuppressive microenvironment and boosting immunotherapy. (May 2022) - Dai, Zan; Wang, Qiaoyun; Tang, Jie; Qu, Rui; Wu, Min; Li, Haoze; Yang, Yannan; Zhen, Xu; Yu, Chengzhong
Abstract: Adenosine and lactate accumulated in tumor microenvironment are two major causes of immunosuppression, their concurrent downregulation holds promise in effective cancer immunotherapy, but remains challenging. Here, a sub-6 nm MnFe2 O4 conjugated with dichloroacetic acid (DCA) nanoparticle is developed to modulate tumor glucose metabolism and ATP catabolism for reversing the tumor immunosuppressive microenvironment. The ultrasmall MnFe2 O4 -DCA nanoparticle can efficiently enter mitochondria and supply oxygen, improving the bioactivity of DCA to regulate glucose metabolism and reduce lactate production ca. 100 times higher than free DCA itself. Moreover, this design significantly downregulates CD39 and CD73 expression than DCA or MnFe2 O4 alone, which consequently decreases the extracellular ATP catabolism. The concurrent regulation of glucose metabolism and ATP catabolism leads to increased immunostimulatory ATP level and decreased immunosuppressive adenosine and lactate levels in tumor microenvironment, eventually amplified dendritic cells maturation, enhanced cytotoxic T lymphocyte response, and improved cancer immunotherapy efficacy.